Use of Vedolizumab in Inflammatory Bowel Disease: A Single-Center Experience - Erdoğan, Çağdaş; Yeşil, Bayram; Bacaksız, Ferhat; Arı, Derya; Gökbulut, Volkan; Yüksel, Mahmut; Özderin Özin, Yasemin; Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2022)
Background: Vedolizumab, which is a monoclonal antibody that selectively binds to α4β7 integrin in the gastrointestinal system, may be an effective and safe treatment alternative in those with anti-tumor necrosis factor-resistant inflammatory bowel disease. Methods: Patients administered vedolizumab due to anti-tumor necrosis factor resistant or anti-tumor necrosis factor side effects between August 2017 and November 2020 were included in the study. Crohn’s patients were evaluated using the Harvey–Bradshaw index and Simple Endoscopic Score for Crohn’s Disease, whereas ulcerative colitis patients were evaluated with the Partial Mayo Score Index and Rachmilewitz score. All patients were followed up for 3 months and their blood samples were taken every 3 months. Hemoglobin, white blood cell, leukocyte, lymphocyte, and platelet counts of the patients were performed. Albumin, C-reactive protein, and erythrocye sedimentation rate values were recorded. The side effect profile for vedolizumab was evaluated for all patients. Among the side effects, arthralgia and flu-like symptoms were observed. Results: A total of 48 patients (18 ulcerative colitis and 30 Crohn’s disease) were included in the study. Vedolizumab therapy was initi- ated in the patients due to anti-tumor necrosis factor resistance (17 ulcerative colitis and 26 Crohn’s disease) or anti-tumor necrosis factor side effects (1 ulcerative colitis and 4 Crohn’s disease). A total of 30 (63%) patients, including 15 (83%) ulcerative colitis and 15 (50%) Crohn’s disease, responded to treatment (both response and remission). The mean duration of response to treatment was 4.5 ± 1.5 months. A total of 20 (42%) patients in the vedolizumab therapy subgroup (10/10, ulcerative colitis/Crohn’s disease) went into remission. The mean Harvey–Bradshaw Index value was 9.8 ± 2.8 in the Crohn’s disease patients at the time of initial treatment. The mean Simple Endoscopic Score for Crohn’s disease value was 11.2 ± 3.1 at the time of initial treatment. The mean Harvey–Bradshaw Index value was 6.5 ± 3.0 and the mean Simple Endoscopic Score for Crohn’s disease value was 4.9 ± 3.6 at 6 months post-treatment. The mean Ulcerative Colitis Endoscopic Index (Rachmilewitz) value was 9.3 ± 1.2 at the time of initial treatment. In addition, the mean Partial Mayo Scoring Index was 6.4 ± 1.5 at the time of initial treatment. The mean Ulcerative Colitis Endoscopic Index (Rachmilewitz) value was 0 (0-6.0), and the mean Partial Mayo Scoring Index was 1.5 (0.3-4.0) at 6 months post-treatment. Conclusion: Vedolizumab therapy is effective in both induction and maintenance of remission in inflammatory bowel disease patients who are resistant to anti-tumor necrosis factor or who can not receive anti-tumor necrosis factor therapy due to side effects. No signifi- cant side effect was observed in the patients during follow-up. Cite this article as: Erdoğan Ç, Yeşil B, Bacaksız F, et al. Use of vedolizumab in inflammatory bowel disease: A single-center experience. Turk J Gastroenterol. 2022;33(10):831-837.